(3GdQSGdI GdecfjI aj GdOhGA HGdcfjIs - (3MSjf Hf Ydj Hf SdjeGf GdMfaj, MSjf NhLI,J (B1169 (3g` s
(3ChdgG (B:s
(3GdMeO ddg HGQj GdfSje CeG HYO ajbhd GdMGL MSjf NhLI GHf Ydi Hf SdjeGf Gfg bO SHb dj eMfI HHdGO GdGaQfL hGLJeYJ eY GdHYV ef MceGFgG hef dg NHQI hfbdJ Yfg ahGFO dWjaI s
(3BNQgG (B:s
(3heG cGf ef GdNVQI cGdaQY hGdQLdI UjakG , hdSGf GdKhQ heG GTHgI TJGA MJj jSJhj ceGd GdUMI GdeYghOI s
(3Vef eLehY , JQJjHgG (B: 12s
(3HgG fXGe GdJYbjHIs
(3Ufa cJGHI HJhfS SfI (B1101(3g` `s
(3IfbdI YTQ ebGdGJ hNGJeIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B609s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs